2016
DOI: 10.1007/s10585-016-9800-3
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue invasion of papillary thyroid carcinoma

Abstract: Extrathyroidal extension (ETE) of papillary thyroid carcinoma (PTC) is common and clinical presentation can vary from minimal to extensive locoregional involvement. Although PTC is generally considered the most benign among all thyroid carcinomas, it may present with local invasion with poor prognosis. Our retrospective study involved 3267 PTC patients undergoing regular follow-up at Chang Gung Medical Center in Linkou, Taiwan. Among them, 269 were PTC cases with ETE, having tumors greater than 1 cm in size an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Lin et al found that patients with ETE demonstrated a lower survival rate than those with intrathyroidal and lymph node metastases. They reported that the mortality rates in patients with extensive ETE and secondary primary malignancy increased to 71.4% (33.3% in those without ETE) 25 . However, this study did not divide the ETE into subgroups.…”
Section: Discussionmentioning
confidence: 75%
“…Lin et al found that patients with ETE demonstrated a lower survival rate than those with intrathyroidal and lymph node metastases. They reported that the mortality rates in patients with extensive ETE and secondary primary malignancy increased to 71.4% (33.3% in those without ETE) 25 . However, this study did not divide the ETE into subgroups.…”
Section: Discussionmentioning
confidence: 75%
“…Tumor metastasis is the major cause of cancer-related deaths [ 5 ]. The development of cancer metastasis involves multiple steps.…”
Section: Introductionmentioning
confidence: 99%
“…31 Its tendency to metastasis is responsible for poor prognosis of PTC patients and is also an important reason for the majority of patient deaths. 11,12 Numerous studies have demonstrated that EMT is a crucial process during cancer progression and metastasis and could be promoted through multiple signaling pathways in cancer cells. 32,33 Thus, exploration of novel agents targeting EMT-associated pathways is urgently needed for PTC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…810 Unfortunately, there still are a small fraction of patients who develop local and distant metastasis and consequently suffer from a low survival rate. 11,12 Therefore, it is desperately needed to have a better understanding of the mechanisms underlying PTC metastasis.…”
Section: Introductionmentioning
confidence: 99%